Representation Of Color Imagery in Usman Nasir's Poetry - Tajibaeva Dilfuza Erkinovna (Zien Journals, 2024)
The article analyzes the poetry of Usman Nasir, one of the talented representatives of 20th century Uzbek literature. It also depicted the poet's skill in the color image used in the poet's poetry.
Keywords: Uzbek poetry; pictorial means; poetic image